From Anthroparasitism to Posthuman Symbiosis: Peggy Karpouzou and Nikoleta Zampaki: Symbiotic Posthumanist Ecologies in Western Literature, Philosophy and Art. Towards Theory and Practice - Lovasz, Adam; Horvath, Mark (Border Crossing, 2024)
Review of Peggy Karpouzou and Nikoleta Zampaki (Eds.) (2023) Symbiotic Posthumanist Ecologies in Western Literature, Philosophy and Art. Towards Theory and Practice. Peter Lang. [ISBN: 9783631882917] 326 pages.